Mycetoma due to Aspergillus flavus in a diabetic patient: Case report and literature review. (2022) - Kamali Sarvestani, Hasti; Ahmadi, Bahram; Gerami Shoar, Mohsen; Getso, Muhammad; Rafat, Zahra; Mahmoudi, Shahram; Khansari, Mahmoud; Salahshour, Faeze; Fatahi, Ladan; Salehi, Mohammadreza; Ansari, Saham
Abstract: Diabetes mellitus patients are prone to cutaneous and subcutaneous fungal infections due to pathogenic fungi, including dermatophytes, Mucorales, Candida, Aspergillus, and Fusarium species. Here, we report a case of A. flavus mycetoma confirmed by isolation and molecular identification. The case was a 38-year-old male farmer with a seven-year history of type 2 diabetes mellitus, living in Khuzestan, southwest of Iran. The patient presented with a right foot swelling associated with a nodule and multiple discharging sinuses following trauma sustained on the foot while working barefoot on the rice farm, a year ago. The nodule appeared at the site of the trauma two months after the injury. The initial diagnosis was based on direct microscopic examination of lesions scraping using 20% potassium hydroxide and radiology. Molecular analysis confirmed the isolates to be A. flavus . In vitro susceptibility of the isolate to voriconazole, posaconazole, caspofungin, itraconazole, and amphotericin B was determined. Treatment with voriconazole (200 mg twice daily) stopped the purulent discharge, reduced the swelling, and improved the clinical condition within two months. The study emphasizes the importance of wearing footwear to prevent skin trauma as the main risk factor of patient involvement.